Heat transfer and stress characteristics of additive manufactured FCCZ lattice channel using thermal fluid-structure interaction model. (March 2020) - Yun, Sungho; Kwon, Junho; Lee, DongChan; Shin, Hyun Ho; Kim, Yongchan
Highlights: Heat transfer and stress characteristics of FCCZ lattice channel are investigated. Thermal fluid-structure interaction (TFSI) one-way coupled model is developed. Heat transfer coefficient and pressure drop increase with decreasing porosity. Heat transfer and structural performances of H13 channel are the highest. Abstract: Lattice channels designed for hot stamping, metal injection, and die casting should have high heat transfer and structural performances. In this study, a thermal fluid-structure interaction (TFSI) one-way coupled model is developed to estimate the heat transfer and stress characteristics of a face-centered cubic with vertical struts (FCCZ) lattice channel. Based on the simulation model, the heat transfer and stress characteristics of the FCCZ lattice channel produced by metal additive manufacturing (AM) are analyzed in terms of the thermal fluid field, convective heat transfer coefficient, pressure drop, and stress distribution by varying the porosity and inlet velocity. Considering the thermal-structural performance factor (TSPF), the optimum porosity of the FCCZ lattice channel is determined as 0.8. In addition, the performances of the FCCZ lattice channels using 17-4 PH, H13, and maraging steel are compared. The performance of the H13 channel is superior to those of the 17-4 PH and maraging steel channels.